Development Of Auction Module Siapsiapnikah.com Using Extreme Programming Method And Crowdsourcing Concept - Fitasari Wiharni; Yuli Adam Prasetyo; Taufik Nur Adi (eProceedings of Engineering, 2015)
Abstract Wedding organizer is a business that provides products or services related to wedding ceremony and arrange their customer wedding. Wedding organizer began use internet as a media to advertise and promote their products and services. Moreover, Indonesia people using internet to get the information about wedding organizer easier. In fact, when the customers find and choose wedding organizer, price is a high priority to considering. In addition to find wedding packages, the customers want to find the products and services except a package and proper to their budget. From that fact, this research will discuss on auction module development of siapsiapnikah.com website application. On develop a module, researcher will apply auction system as a solution to find suitable price on wedding products and services. To implement auction system in the website properly, researcher using crowdsourcing concept to get more price from more than one w edding organizer on a customer needs. Furthermore, researchers use Extreme Programming as a developing method and Codeigniter as a framework. The result of this research is a website application that has auction system to help customer finding suitable wedding organizer and price. The customers will get prices from many wedding organizer depends on customer needs. Keyword: crowdsourcing, codeigniter, extreme programming, online auction, wedding organizer.